Does better, cheaper day care make for more satisfied parents? - Georg F. Camehl; Juliane F. Stahl; Pia S. Schober; C. Katharina Spieß (DIW Economic Bulletin, 2015)
Following the major expansion of day care provision in Germany in recent years, the quality of these programs has increasingly also been the subject of public debate. When evaluating the quality of German day care centers, experts have frequently concluded that there is considerable room for improvement. Apart from considering expert opinions, it is also interesting to look at how parents rate the quality of day care centers and whether this differs according to level of income or education. The present article primarily focuses on parental satisfaction with various quality aspects. To determine this, data from an extension study are analyzed for the first time, surveying parents from the Socio-Economic Panel (SOEP) study and the Families in Germany (Familien in Deutschland, FiD) study whose children attend a day care center. We examine satisfaction with different aspects related to organization, equipment and resources, pedagogic staff, activities with the children, cooperation with parents, and, specifically, cost. A supplementary analysis on potential willingness to pay, depending on household income, provides us with additional information on the extent to which parents would be prepared to pay more for a day care place for their child. [...]
Keywords: I24; I28; J13; 330; child care; early education; day-care quality; satisfaction; well-being; socio-economic differences; parents